Associations between self-efficacy and sedentary behaviour: a meta-analysis. Issue 3 (4th March 2021) - Szczuka, Zofia; Banik, Anna; Abraham, Charles; Kulis, Ewa; Luszczynska, Aleksandra
Abstract: Objective: The study sought to synthesize research on the relationship between time spent engaged in sedentary behaviours (SB) and self-efficacy. Analyses investigated whether such associations are moderated by age, conceptualization of self-efficacy, conceptualization of SB, and/or SB measurement. Design and Main Outcome Measures: The review was registered with PROSPERO (no. CRD42018086899). Studies including associations between self-efficacy and SB were identified through a systematic search of six databases. Inclusion criteria were met by k = 26 original studies. Results: A random effect meta-analysis showed that higher levels of self-efficacy were associated with lower levels of SB ( r = −.158, 95% CI [−.220, −.094]). Moderator analyses indicated that associations between self-efficacy and SB may be similar in strength across age groups, the conceptualizations of self-efficacy or SB and SB measurements. Conclusion: The findings provide preliminary guidance for future interventions targeting reduction of SB, although more longitudinal research is needed to draw causal inferences.